An assessment of the waste-to-energy potential of municipal solid wastes in Ethiopia. (September 2022) - Misganaw, Awoke; Teffera, Belay
Abstract: Ethiopia is one of the fastest-growing economies in the world. This rapid development is aggravating the ever-increasing gap between demand and supply of energy. The conversion of waste-to-energy is considered a suitable waste management strategy both to minimize dependency on nonrenewable energy sources and their associated detrimental environmental impacts. In this study, the potential for energy production from existing and projected municipal solid waste (MSW) in Ethiopia was estimated using mass burn and mass burn with recycling scenarios. The analysis shows that the amount of energy generated from mass burn and mass burn with recycling scenarios in the year 2060 will be 376, 398.9 and 62, 733.1 megawatts (MW), respectively. Population growth, waste generation, and energy production have strong positive relationships with their correlation coefficient values greater than 0.80. The estimated energy production potential of the country from the two scenarios can be used as an input to design future waste-to-energy facilities. Graphical abstract: Unlabelled Image Highlights: MSW composition is critical to determine most effective waste-to-energy technique. MSW management strategy using renewable energy production technologies Mass burn and mass burn with recycling scenario aspects of waste-to-energy The present and future energy potential of MSW in Ethiopia is analyzed.